2023
DOI: 10.1007/s00894-023-05569-6
|View full text |Cite
|
Sign up to set email alerts
|

Bioprospecting phytochemicals of Rosmarinus officinalis L. for targeting SARS-CoV-2 main protease (Mpro): a computational study

Abstract: Context The persistent spread of highly contagious COVID-19 disease is one of the deadliest occurrences in the history of mankind. Despite the distribution of numerous efficacious vaccines and their extensive usage, the perpetual effectiveness of immunization is being catechized. Therefore, discovering an alternative therapy to control and prevent COVID-19 infections has become a top priority. The main protease (M pro ) plays a key role in viral replication, making it an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Chlorogenic acid and rosmarinic acid showed many chemical interactions with 6LZG. These two compounds, chlorogenic acid and rosmarinic acid, were docked against the SAR-Cov 2 protein 6LZG and it was noted these compounds showed a good binding affinity and appreciable hydrogen bonding interactions with amino acid residues of the protein ( Adem S. E. et al, 2021 ; Jahan et al, 2021 ; Patel et al, 2023 ).…”
Section: Resultsmentioning
confidence: 99%
“…Chlorogenic acid and rosmarinic acid showed many chemical interactions with 6LZG. These two compounds, chlorogenic acid and rosmarinic acid, were docked against the SAR-Cov 2 protein 6LZG and it was noted these compounds showed a good binding affinity and appreciable hydrogen bonding interactions with amino acid residues of the protein ( Adem S. E. et al, 2021 ; Jahan et al, 2021 ; Patel et al, 2023 ).…”
Section: Resultsmentioning
confidence: 99%
“…A molecular docking analysis was performed to assess the binding affinity of 30 compounds extracted from rosemary to the SARS-CoV-2 main protease in comparison to remdesivir and favipiravir as positive controls. Mostly, apigenin, diosmin, betulinic acid, luteolin, and carnosol showed potent binding affinity for M pro , which indicates the possibility of using rosemary as an inhibitor and blocker of the SARS-CoV-2 life cycle by disrupting its replication inside the host [ 141 ]. Moreover, another molecular docking in silico analysis performed on different plants, including Rosmarinus officinalis , Thymbra spicata , Satureja thymbra , and Stachys lavandulifolia plants, showed that rosmarinic acid and rosmanol, which are found mostly in rosemary, hold a high potential to inhibit M pro and ACE2.…”
Section: Rosmarinus Officinale ( R Officinale ...mentioning
confidence: 99%
“…One of the most famous inhibitors is N3 (PubChem CID 6323191) [17]. Many studies focus on repurposing known antiviral drugs [36,[40][41][42][43][44][45], or on studying natural compounds [46][47][48][49][50]. Such an approach has several advantages, namely, reducing the chance of candidate failure or shortening the development time and cost.…”
Section: Introductionmentioning
confidence: 99%